PENERAPAN MODEL PEMBELAJARAN BIOLOGI BERBASIS READING – CONCEPT MAP –TEAMS GAMES TOURNAMENTS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR KOGNITIF SISWA KELAS X IPA 4 SMA LABORATORIUM UM - Ardian Anjar Pangestuti; Herawati Susilo; Siti Zubaidah (Universitas Sebelas Maret, 2014)
This research aims to enhance critical thinking skills and cognitive learning outcomes of students of class X IPA 4 SMA Laboratorium UM, through the aplication of Biology learning model based on Reading – Concept Map – Teams Games Tournaments. This research is a Classroom Action Research (CAR) which consisted of two cycles. Cycle I carried as many as eleven times of meetings and the cycle II carried as many as twelve times of meetings. The subjects of this research are the 31 of class X IPA 4 SMA Laboratorium UM, comprising 11 male students and 12 female students. The increased results of the students’s critical thinking abilities can be seen from the end of the cycle test as follows. The test results were analyzed using critical thinking skills assessment rubric adapted from Hart. The assessment is done on the basis of some musty among other truths answers given, the ability to provide the right answers and reasons and in accordance with the order of the sentences logically correct and proper language rules. Cognitive learning outcomes data obtained from the test results were analyzed using the answer key cognitive learning outcomes based on the truth of the material.This research shows that the results, critical thinking skills of students has increased from cycle I to cycle II. In the cycle I, the class average grade is 46,22; while in the cycle II, the class average grade is 72,71. As in critical thinking ability, the increased cognitive learning outcomes also can be known from the end of the cycle test results. In the cycle I, it has a class average grade of 49,74; while in cycle II, it has a class average grade of 69,69. Keywords: Biology Learning Model Based on Reading – Concept Map – Teams Games Tournaments, Critical Thinking Skills, Cognitive Learning Outcomes